Dietary characteristics associated with plasma concentrations of per- and polyfluoroalkyl substances among adults with pre-diabetes: Cross-sectional results from the Diabetes Prevention Program Trial. (April 2020) - Lin, Pi-I D.; Cardenas, Andres; Hauser, Russ; Gold, Diane R.; Kleinman, Ken P.; Hivert, Marie-France; Fleisch, Abby F.; Calafat, Antonia M.; Sanchez-Guerra, Marco; Osorio-Yáñez, Citlalli; Webster, Thomas F.; Horton, Edward S.; et al.
Highlights: We evaluated dietary characteristics among 941 prediabetic adults in the USA. Vegetable diet pattern had inverse association with plasma MeFOSAA concentration. Meat/fish/shellfish pattern had positive associations with most plasma PFAS. Low-fiber and high-fat grains intake had positive associations with some PFAS. Coffee/tea consumption had positive association with plasma PFOA concentration. Abstract: Diet is assumed to be the main source of exposure to per- and polyfluoroalkyl substances (PFAS) in non-occupationally exposed populations, but studies on the diet-PFAS relationship in the United States are scarce. We extracted multiple dietary variables, including daily intakes of food group, diet scores, and dietary patterns, from self-reported dietary data collected at baseline (1996–1999) from adults with pre-diabetes enrolled in the Diabetes Prevention Program, and used linear regression models to evaluate relationships of each dietary variable with plasma concentrations of six PFAS (perfluorooctane sulfonic acid (PFOS), perfluorooctanoic acid (PFOA), perfluorohexane sulfonic acid (PFHxS), 2-(N-ethyl-perfluorooctane sulfonamido) acetic acid (EtFOSAA), 2-(N-methyl-perfluorooctane sulfonamido) acetic acid (MeFOSAA), perfluorononanoic acid (PFNA) adjusting for covariates. Participants (N = 941, 65% female, 58% Caucasian, 68% married, 75% with higher education, 95% nonsmoker) had similar PFAS concentrations compared to the general U.S. population during 1999–2000. Using a single food group approach, fried fish, other fish/shellfish, meat and poultry had positive associations with most PFAS plasma concentrations. The strongest effect estimate detected was between fried fish and PFNA [13.6% (95% CI: 7.7, 19.9) increase in median concentration per SD increase]. Low-carbohydrate and high protein diet score had positive association with plasma PFHxS. Some food groups, mostly vegetables and fruits, and the Dietary Approaches to Stop Hypertension diet score had inverse associations with PFOS and MeFOSAA. A vegetable diet pattern was associated with lower plasma concentrations of MeFOSAA, while high-fat meat and low-fiber and high-fat grains diet patterns were associated with higher plasma concentrations of PFOS, PFHxS, MeFOSAA and PFNA. We summarized four major dietary characteristics associated with variations in PFAS plasma concentrations in this population. Specifically, consuming more meat/fish/shellfish (especially fried fish, and excluding Omega3-rich fish), low-fiber and high-fat bread/cereal/rice/pasta, and coffee/tea was associated with higher plasma concentrations while dietary patterns of vegetables, fruits and Omega-3 rich fish were associated with lower plasma concentrations of some PFAS.